PENGARUH PROMOSI DAN PELAYANAN TERHADAP KEPUASAN PENYEWA PERLENGKAPAN COSPLAY DI COSPLAYRENTALKU KENDARI - Firlyana, Iin; Fadhillah, Is (Bisnis-Net, 2024)
This study aims to examine the effect of promotion and service quality on customer satisfaction who rent at Cosplayrentalku Kendari. The method used in this research is a quantitative method by distributing questionnaires to 60 respondents The respondents of the study were 60 respondents The sampling technique used in this study used purposive sampling technique. The results showed that promotion and service partially and simultaneously had a positive and significant influence on customer satisfaction Cosplayrentalku Kendari.